2017
DOI: 10.1038/s41598-017-07056-4
|View full text |Cite
|
Sign up to set email alerts
|

Response of cotton phenology to climate change on the North China Plain from 1981 to 2012

Abstract: To identify countermeasures for the impacts of climate change on crop production, exploring the changes in crop phenology and their relationship to climate change is required. This study was based on cotton phenology and climate data collected from 13 agro-meteorological experimental stations and 13 meteorological stations on the North China Plain from 1981 to 2012. Spatiotemporal trends in the cotton phenology data, lengths of the different growing phases, mean temperatures, and rainfall were analyzed. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Increased temperature speeds growth, which leads to reduced yield. Ahmad et al 94 , Huang and Ji 95 and Wang et al 96 reported negative correlations of temperature rise with all the phenological stages besides cotton yield in central and lower Punjab regions of Pakistan. They further reported that about 30% of the negative consequences of climate warming are compensated by sowing new cotton cultivars with high thermal requirements.…”
Section: Impact Of Climate Warming On Phenological Shiftmentioning
confidence: 98%
“…Increased temperature speeds growth, which leads to reduced yield. Ahmad et al 94 , Huang and Ji 95 and Wang et al 96 reported negative correlations of temperature rise with all the phenological stages besides cotton yield in central and lower Punjab regions of Pakistan. They further reported that about 30% of the negative consequences of climate warming are compensated by sowing new cotton cultivars with high thermal requirements.…”
Section: Impact Of Climate Warming On Phenological Shiftmentioning
confidence: 98%
“…Such shifts in plant density and the reallocation of sowing date management might help high-temperature areas such as Punjab, Pakistan and some parts of China. In the North China Plain (NCP) cotton belt, it was also discovered that the planting dates, seed emergence, squaring, flowering, and boll opening days were earlier by 0.25, 1.39, 0.92, 2.81, and 0.83 decade −1 [20,21].…”
Section: Plant Functioning Under Extreme Temperaturementioning
confidence: 99%
“…Meanwhile, in Xinjiang, the plantation is smart and highly mechanized. The escalating temperature in cotton areas increases evapotranspiration rates, sometimes causing severe water stress [21,29] and fruit abscission, thus reducing plant growth and yield. The influence of elevated variations in the rain from mean values negatively resulted in the productivity of cotton.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, temperature, precipitation, and sunshine hours are the most important climatic factors to meet the demand of water, light, and heat resource for crop growth 17 . Previous research has emphasized the effects of temperature 5 , 11 , 28 , whereas the impact of other important climatic factors especially precipitation and sunshine hours upon soybean growth periods remain largely unknown 12 , 18 , 29 , which can increase uncertainty of results. Moreover, studies of temperature’s effect on soybean growth and yield were mainly performed at a local scale 30 , 31 , while less attention has been given to the spatiotemporal variation in changes of soybean phenology and its responses to climate change among different cultivation regions, which is critical to guide regional climate adaptation strategies and estimate the spatial heterogeneity of soybean production.…”
Section: Introductionmentioning
confidence: 99%